What drive innovation activity in developing countries? - Tee, Chee Lip; Wan Ngah, Wan Azman Saini; Ibrahim, Saifuzzaman (School of Economics, Faculty of Economics and Management, Universiti Kebangsaan Malaysia, 2015)
This paper seeks to provide an empirical assessment of the determinants of innovative activity across developing countries by focusing on the roles of trade and capital account openness. The Extreme-Bound-Analysis (EBA) approach is applied to data from 58 countries over the 1996-2011 period. The results reveal that human capital is a robust determinant of innovation activity. Meanwhile, the impact of foreign technology inflow is found to be different depending on the indicators used. The results indicate that import of machinery and equipment is a robust determinant of innovation but the impacts of total import, import of manufactured goods, and FDI inflows appear to be fragile.